Pengaruh Pengetahuan Investasi, Modal Minimal, Return, Uang Saku, dan Manfaat Investasi Terhadap Minat Mahasiswa Berinvestasi Di Pasar Modal Syariah - Wahyudi, Rizky; Soemitra, Andri; Harahap, Muhammad Ikhsan (Jurnal Manajemen Akuntansi (JUMSI), 2023)
If a person just saves money, the value of that money will decrease over time. One of the main reasons Indonesians need to plan their finances is that they need to invest for their future. Investment is an essential part of economic growth and development in any country. This helps businesses grow and creates jobs, which in turn helps grow the economy. Young people can help drive this outcome by participating in government projects designed to attract new investors to the country, especially students. This will help drive economic growth and make the country more prosperous. This study aims to analyze the influence of investment knowledge, minimum capital, returns, risks and benefits on students' interest in investing in Medan. This research is focused on undergraduate students of the Faculty of Economics and Economics, University of Medan, whose university has an Investment Gallery on the Indonesia Stock Exchange (GI-BEI) with a student population of 22,010 students. This research used convenience sampling, meaning that the respondents were chosen because they matched the researcher. Taking a sample of 100 people produces data which is analyzed using descriptive analysis and multiple regression analysis. The results of this study indicate that having knowledge about investment, minimum capital, return, pocket money and investment benefits has a positive effect on student interest in investing in Medan. Based on the results of Adjusted R Square of 84.8 percent, it is suggested that further research be carried out using other variables.